Industrial Training Report: Perpustakaan Tun Abdul Razak (PTAR) Universiti Teknologi Mara (UiTM) Cawangan Pulau Pinang / Nur Husna Hashim - Hashim, Nur Husna (Faculty of Information Management, 2018)
This academic writing report is based on the industrial training undergone by trainee for five (5) months starting from 151 of August 2018 until 3/51 of December 2018 at Perpustakaan Tun Abdul Razak (PTAR) Universiti Teknologi MARA (UiTM) Cawangan Pu/au Pinang Kampus Permatang Pauh. The purpose of this academic writing is to represent the detailed information of trainee's experience and lesson learnt in the field of Library Management during the internship. The findings of the reports include the organization's profile as a whole, all training activities involve by trainee, the completed special project created by trainee, and also few recommendations suggest to the management of PTAR Permatang Pauh. E-bul!etin and exhibition project has been done as a trainee's special project while undergone the industrial training at PTAR Permatang Pauh. During the internship also trainee has gained a lot of valuable knowledge and experiences although it is a liltle bit challenging on the early of the internship training. At the end of the training, trainee has completed all the task given by the PTAR UiTM Cawangan Pu/au Pinang Kampus Permatang Pauh and completed the special project.